2020
DOI: 10.1186/s40942-020-00261-w
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of uveal melanoma in Brazil

Abstract: Purpose To report the prevalence of uveal melanoma in a Hospital database in Brazil over the period of 16 years (2000 to 2016). Design Descriptive epidemiological study evaluating the Brazilian Hospital Based Cancer Registries. Participants/methods Uveal melanomas were identified based on ICD-O-3 codes C69.3 [choroid], C69.4 [ciliary body and iris], and C69.2 [retina]) derived from the Integrator Registry database. Kolmogorov–Smirnov Test was used for evaluation of normality of data, t-test and Chi square … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…It has been mentioned that uveal melanoma was more incident in men 11 . Nevertheless, an epidemiological study in Brazil on the incidence of uveal melanoma found higher incidence of this type of tumor in women similar to the case described 12 . However, the difference in the proportion between men and women in the study was not very high.…”
Section: Discussionsupporting
confidence: 78%
“…It has been mentioned that uveal melanoma was more incident in men 11 . Nevertheless, an epidemiological study in Brazil on the incidence of uveal melanoma found higher incidence of this type of tumor in women similar to the case described 12 . However, the difference in the proportion between men and women in the study was not very high.…”
Section: Discussionsupporting
confidence: 78%
“…1,3,6 Other risk factors associated with ocular melanoma include sex, Caucasian origin, light skin and iris pigmentation, genetic predisposition (BAP1 mutation), environmental factors, and certain dermatological conditions like dysplastic nevus syndrome or nevus of Ota. [11][12][13][14] Despite the fact that the treatment of ocular melanoma has evolved with a therapeutic shift to eye-conserving treatment options, it is estimated that still more than 50% of patients develop metastases within 25 years from the initial diagnosis. Poor prognosis indicators include older age at diagnosis, large tumor diameter, anterior location, extraocular extension, histopathological type, and cytogenetic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic features, such as chromosome 3 monosomy and the mutations in the GNAQ and BAP1 genes, are also related to higher aggressiveness and systemic spread. Recently, PALB2 and MLH1 germline mutations were associated with a hereditary predisposition to the risk of uveal melanoma, and several other genes also have potential associations with uveal melanomas[ 15 ]. The clinical presentation of uveal melanoma relies on the mass location within the uveal tissue, size, pigmentation, associated bleeding, retinal detachment, inflammation, and extrascleral extension.…”
Section: Discussionmentioning
confidence: 99%